Managemental practices and welfare of pack animals in middle Himalayan region of India - TANUSHA, TANUSHA; TIWARI, RUPASI; BHARTI, P K; DUTT, TRIVENI (The Indian Journal of Animal Sciences, 2016)
The results revealed that most of the owners provided all kind of feed to the pack animals but there was variation in amount of feeds during work and rest. Majority of them provided Kutcha type shelters to pack animals with less adequate heights and floor space areas. Majority of the equines had dry matted coat, normal mucous membrane, no limb deformity, free from ectoparasties and about 75% of them had scars on their body, alert aptitude and almost all animals were friendly to owners. They carried load of 100 kg on back of animals and majority of them (55%) used the animals for 6–9 h with rest in between. The owners put best efforts to keep the animals in the best way. The farmers followed all the routine practices recommended for pack animal rearing, although most of them were not aware of the scientific rearing practices. Most of the farmers consulted a veterinarian for treatment. However, they also exploited the animals and did not follow the norms made by the government, therefore, the pack animal owners need to be trained as per the scientific recommendation for better management practices of the pack animals so that they can utilize these animals to their maximum potential for enhancing livelihood without compromising with the welfare measures.